Identification of novel genomic imbalances in Saudi patients with congenital heart disease - Al-Hassnan, Zuhair N. (Mol Cytogenet, 2018)
BACKGROUND: Quick genetic diagnosis of a patient with congenital heart disease (CHD) is quite important for proper health care and management. Copy number variations (CNV), chromosomal imbalances and rearrangements have been frequently associated with CHD. Previously, due to limitations of microscope based standard karyotyping techniques copious CNVs and submicroscopic imbalances could not be detected in numerous CHD patients. The aim of our study is to identify cytogenetic abnormalities among the selected CHD cases (n = 17) of the cohort using high density oligo arrays. RESULTS: Our screening study indicated that six patients (~35%) have various cytogenetic abnormalities. Among the patients, only patient 2 had a duplication whereas the rest carried various deletions. The patients 1, 4 and 6 have only single large deletions throughout their genome; a 3.2 Mb deletion on chromosome 7, a 3.35 Mb deletion on chromosome 3, and a 2.78 Mb a deletion on chromosome 2, respectively. Patients 3 and 5 have two deletions on different chromosomes. Patient 3 has deletions on chromosome 2 (2q24.1; 249 kb) and 16 (16q22.2; 1.8 Mb). Patient 4 has a 3.35 Mb an interstitial deletion on chromosome 3 (3q13.2q13.31). Based on our search on the latest available literature, our study is the first inclusive array CGH evaluation on Saudi cohort of CHD patients. CONCLUSIONS: This study emphasizes the importance of the arrays in genetic diagnosis of CHD. Based on our results the high resolution arrays should be utilized as first-tier diagnostic tool in clinical care as suggested before by others. Moreover, previously evaluated negative CHD cases (based on standard karyotyping methods) should be re-examined by microarray based cytogenetic methods.